Effect of humidity on the vibrating membrane of the python skin and eco-friendly materials imitation skin on traditional Chinese musical instrument – leiqin - Yeoh, Pei Sze; Mohamed Razali, Camellia Siti Maya; Zhang, Zixue (Leadership Academy of Social Sciences, 2024)
This paper presents an alternative possibility to the use of eco-friendly material on the vibrating membrane of a traditional Chinese musical instrument – leiqin. The study investigated on four soundboxes covered with python skin (representing the original material used for the vibrating membrane of the leiqin), and the remodeled eco-friendly imitation skin (the main component is polycarbonate membrane), each with the same diameter, placed under 4 different relative humidity conditions (30%RH, 50%RH, 70%RH, and 90%RH) inside a climate chamber. The sound intensity measured at every 8 hours for a total of 48 hours. In addition, both the python and imitation skins were soaked in water for 24 hours and weighed. Results indicated that the vibrating membrane using python skin exhibited high sensitivity to humidity, resulting in a wide change range of sound intensity and increased weight. Conversely, the imitation skin's vibratory membrane was unaffected by humidity. In summary, the eco-friendly imitation skin surpassed that of the python skin. Implications of this study are discussed.